2018
DOI: 10.1071/sh18065
|View full text |Cite
|
Sign up to set email alerts
|

Princess PrEP program: the first key population-led model to deliver pre-exposure prophylaxis to key populations by key populations in Thailand

Abstract: Background No data are available on the feasibility of pre-exposure prophylaxis (PrEP) delivered by trained key population (KP) community health workers. Herein we report data from the KP-led Princess PrEP program serving men who have sex with men (MSM) and transgender women (TGW) in Thailand. Methods: From January 2016 to December 2017, trained MSM and TGW community health workers delivered same-day PrEP service in community health centres, allowing clients to receive one PrEP bottle to start on the day of HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 19 publications
3
119
0
1
Order By: Relevance
“…These findings indicated that decentralization of ART service to non‐conventional service delivery sites, such as a KP‐led CBO where non‐judgemental services including HIV testing, PrEP and PEP are delivered by lay providers who are familiar with lifestyles and needs of these subgroups of KP, has high potential to support the roll‐out of HIV self‐testing . PrEP uptake among Online Group participants was comparable to previously reported uptake among MSM and TGW in Thailand . More than two‐thirds of our participants in the Offline and Online groups received services at the CBOs.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These findings indicated that decentralization of ART service to non‐conventional service delivery sites, such as a KP‐led CBO where non‐judgemental services including HIV testing, PrEP and PEP are delivered by lay providers who are familiar with lifestyles and needs of these subgroups of KP, has high potential to support the roll‐out of HIV self‐testing . PrEP uptake among Online Group participants was comparable to previously reported uptake among MSM and TGW in Thailand . More than two‐thirds of our participants in the Offline and Online groups received services at the CBOs.…”
Section: Discussionsupporting
confidence: 60%
“…A study in Vietnam also demonstrated that linkages to HIV confirmatory testing and ART among MSM self‐testers, with support from MSM lay providers, could be as high as 91% and 90% respectively . These findings indicated that decentralization of ART service to non‐conventional service delivery sites, such as a KP‐led CBO where non‐judgemental services including HIV testing, PrEP and PEP are delivered by lay providers who are familiar with lifestyles and needs of these subgroups of KP, has high potential to support the roll‐out of HIV self‐testing . PrEP uptake among Online Group participants was comparable to previously reported uptake among MSM and TGW in Thailand .…”
Section: Discussionmentioning
confidence: 99%
“…Six articles had an exclusive focus on MSM as a target group [39][40][41][42][43][44]. Five articles had a focus on the combination of MSM and TGW [45][46][47][48][49]. One study focused exclusively on TGW [50], one on female sex workers (FSW) [51], one on men and women in a serodiscordant relationship [52], one on pregnant or postpartum women [53] and one study focused exclusively on youth (11-24 years old) at risk of HIV acquisition [54].…”
Section: Key Population-speci C Modelsmentioning
confidence: 99%
“…providing care adapted to the needs and demands of the community. These often included services for sexual health in general, including PrEP, and targeted TGW, MSM, FSW and youth in particular [49][50][51]54]. In policy reports of Kenya, Zimbabwe and South Africa, CHCs were mentioned as a possible PrEP delivery site tting their decentralisation strategy for the provision of PrEP [25,28,32,37].…”
Section: Community-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation